2013
DOI: 10.2478/johr-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Fruits Morphology, Chemical Composition and Colour Changes in Must During Maceration of Three Grapevine Cultivars

Abstract: The study compares morphology of clusters and fruits, the chemical composition and changes of pulp in the process of maceration of grape cultivars ‘Mavrud’, ‘Pinot Noir’ and ‘Merlot’. The cultivar ‘Mavrud’ had biggest clusters and fruits. Its fruits were less firm but had the highest acidity while the fruits of the ‘Pinot Noir’ had the highest content of soluble solids and dry matter and the greatest firmness but the lowest acidity and content of nitrites and nitrates. The fruits of the ‘Merlot’ cultivar had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
1
12
2
Order By: Relevance
“…26.1%, range 22.2 -28.8) and moisture (avg. 92.3%, range 85.6 -98.6) contents in eight grape berry cvs are not in agreement with those reported by several authors (Karasu et al, 2016;Kurt et al, 2017;Ochmian et al, 2013;. Notably, Lijavetzky et al (2012) also reported a low DM content (avg.…”
Section: Physicochemical Parameters Of the 'Karaerik' Grape Berrycontrasting
confidence: 68%
See 1 more Smart Citation
“…26.1%, range 22.2 -28.8) and moisture (avg. 92.3%, range 85.6 -98.6) contents in eight grape berry cvs are not in agreement with those reported by several authors (Karasu et al, 2016;Kurt et al, 2017;Ochmian et al, 2013;. Notably, Lijavetzky et al (2012) also reported a low DM content (avg.…”
Section: Physicochemical Parameters Of the 'Karaerik' Grape Berrycontrasting
confidence: 68%
“…The TA in the present grape berry was also in good agreement with ranges reported for 33 grape berries (avg. 4.3, range 0.3 -11.6 CAE g kg −1 fw) in various studies (Ejsmentewicz et al, 2015;Ochmian et al, 2013;Pavlousek & Kumsta, 2011;Rolle et al, 2013;Yamamoto et al, 2015). However, data re-ported for dry matter (avg.…”
Section: Physicochemical Parameters Of the 'Karaerik' Grape Berrymentioning
confidence: 90%
“…26.1%, range 22.2 -28.8) and moisture (avg. 92.3%, range 85.6 -98.6) contents in eight grape berry cvs are not in agreement with those reported by several authors (Karasu et al, 2016;Kurt et al, 2017;Ochmian et al, 2013;. Notably, Lijavetzky et al (2012) also reported a low DM content (avg.…”
Section: Physicochemical Parameters Of the 'Karaerik' Grape Berrymentioning
confidence: 60%
“…1 -26.6, avg. 276.3, range 69.4 -605 g mm −1 , respectively) described in other studies (Conner, 2013;Ochmian et al, 2013;Ejsmentewicz et al, 2015;Yamamoto et al, 2015;Eyduran et al, 2015;Xu et al, 2017).…”
Section: Physicochemical Parameters Of the 'Karaerik' Grape Berrymentioning
confidence: 70%
See 1 more Smart Citation